Eosinophilic leukemoid reaction in a male adolescent with Löeffler syndrome - Bayhan Gulsum Iclal; Mesut Garipardic; Kamuran Karaman; Sinan Akbayram (Lung India, 2015)
The Löeffler syndrome is characterized by pulmonary infiltrates on a chest x-ray accompanied with peripheral eosinophilia. In this article, we have highlighted the Löeffler syndrome complicated with a eosinophilic leukemoid reaction in a previously healthy boy. The patient was treated with albendazole for five days, with a successful result. In countries where parasitic diseases are endemic, the Löeffler syndrome must always be considered in patients who present with a eosinophilic leukemoid reaction.